Mathematical modeling of gantry cranes under seismic excitation and verification with shake table tests - Azeloglu, C. Oktay; Kenan, Hamit; Edincliler, Ayse (TAYLOR & FRANCIS INC, 2023)
Assessment of dynamic behavior of the gantry cranes by using mathematical modeling and shaking table tests is the subject of this study. In this context, the study was carried out in two stages through theoretical and experimental studies. In the theoretical study, a four degrees-of-freedom nonlinear mathematical model which represents the seismic behavior of gantry cranes was developed. In the experimental study, a 1/50 scaled crane model of a prototype crane with respect to dynamic equivalence principle was designed and constructed. Within the scope of theoretical and experimental study, the real earthquake and sine sweep motions were used as input data. To verify the mathematical model, the results of the experimental study were used. Comparison of the mathematical model with the experimental study for the gantry crane structure showed reasonable results. This study shows that dynamic analysis can be done with mathematical modeling of this kind of cranes theoretically. In this way, the dynamic analysis required for a crane which is still in the design phase will be made in a short time and it will be possible to apply the necessary changes and see their effects.
Keywords: Gantry crane; nonlinear mathematical model; shake table tests; structural vibrations; NONLINEAR STRUCTURAL SYSTEM; FUZZY-LOGIC CONTROL; CONTAINER CRANES; VIBRATION CONTROL; SIMILITUDE; EARTHQUAKE; DYNAMICS; CONTROLLER; ATMD; Mechanics